Guatemala : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1998)
This paper reviews economic developments in Guatemala during 1990-97. During 1992-97, Guatemala's economic performance strengthened, with growth rates averaging 4 percent helped by declining inflation, progress in trade and financial reform, and favorable terms of trade. Efforts to improve fiscal and credit policies contributed to reducing the external current account deficit and strengthening the net international reserve position. The authorities succeeded in bringing the combined public sector position to balance in 1995-96. The tax effort was raised from less than 7 percent of GDP in 1994 to 8.7 percent of GDP in 1996.